Marketing 4.0 Elements dalam Peningkatan Customer Loyalty Melalui Customer Satisfaction - Dora Puspita (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
This study aims to examine the impact of elements in 4.0 marketing, namely Brand Identity, Brand Image, Brand Integrity, and Brand Interaction, on Customer Satisfaction and Customer Loyalty. Based on the phenomenon and previous studies, this research identifies a gap in the literature regarding the relationship between 4.0 marketing elements and their impact on consumer satisfaction and loyalty. This type of research is explanatory research with an associative approach, aimed at explaining and testing hypotheses related to the relationships between variables. The research population consists of all Priority customers of BRI Cepu Branch, with a sample of 174 respondents selected using a non-probability sampling technique, specifically convenience sampling. Variable measurement was conducted through a questionnaire with a 1-5 Likert scale, and the data were analyzed using Partial Least Square (PLS) method. The results indicate that Brand Identity, Brand Image, Brand Integrity, and Brand Interaction positively and significantly influence Customer Satisfaction, which, in turn, positively and significantly affects Customer Loyalty. These findings emphasize the important role of 4.0 marketing elements in enhancing consumer satisfaction and loyalty. This study contributes to strengthening 4.0 marketing theory and provides insights for managerial practices in managing brand elements to improve customer satisfaction and loyalty.